Here's the question you clicked on:
ursularoxursox
2x^2-x-3=0 I got x=0 x=-3/2 Did i solve correctly?
0 cannot be the solution I think..
Put 0 back in the equation in place of x, you will not get 0...
I dnt thnk x=0 is right. \(2x^2-x-3=0\) \(2x^2-3x+2x-3=0\) \(x(2x-3)+1(2x-3)=0\) \((x+1)(2x-3)=0\) \(x+1=0 ~or ~ 2x-3=0\)
Getting @ursularoxursox
i'm still having a difficult time understanding the equation
i understand now. thanks for the help everyone!
If anythng is not clear plz ask:)
I think I did another one wrong, can someone please guide me? The equation is 6x^2-5x-4=0 The first time I solved I got x=5/6 and x=-1 The second time I solved I got x=-1/6 and x=4 I don't think either are correct